Selected Papers from the 9th Greek Conference of Biochemistry and Physiology of Exercise - Mougios, Vassilis (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book contains selected papers from the 9th annual conference of the Hellenic Society of Biochemistry and Physiology of Exercise (2019). Exercise biochemistry and exercise physiology are two closely related sport sciences that examine how muscle activity alters the way our bodies (and those of other animals) function at the levels of molecules, cells, organs, and whole body. Included in the book is original research on biochemical and physiological adaptations of children, adolescents, and adults to exercise training; on the use of biochemical and physiological tests to assess sport performance; and on how exercise can fight disease.